SASI MASJID DAN ADAT: Praktik Konservasi Lingkungan Masyarakat Minoritas Muslim Raja Ampat - Ismail Suardi Wekke (IAIN Ponorogo, 2015)
Abstract: This research is to explore the relationship between the mosque and communities in Raja Ampat. Based on the research objectives mentioned, the problems raised in this research is how the community cares in protecting the environment originating from religious expression. Furthermore, this study will describe the condition of the village in running its tradition. The results showed that the villagers have made the Islamic tradition as their references and regulations in keeping the surrounding environment including the sea and the forest. The regulations enforced to community were to guide the community or residents to improve and maintain the production of the environment. Some ideas which were applied in this community were to serve as guidelines for everyone for all the time. Regulations based on the political policies also became a part of the support for this practice with the enactment of local regulations. The regulation was adopted on the basis of the practices and customs of the people that have taken place since long time ago. This research showed that Islam was used as a spirit to support the sustainability of people's habits. The power of religion became the basis in setting the needs and at the same time it could accelerate new ideas to be accepted in the community. This study was to construct the idea that there were some local conditions especially to form an understanding of society in the process of protecting the environment. Finally, this research concludes that religion becomes a rule that arises natural synergy at the needs of the community. In addition, this research becomes the basis for further research on religious expressions and environmental safeguards.الملخص :هذا البحث يبين أهمية المسجد فى المجتمع راجا أمفا (Raja Ampat) . أما مشكلات البحث فهي: كيف اهتمام الجماعة فى تنمية البيئة. فيكون هذا البحث شرحًا لنا عن تطبيق عناصر العادات فى القرية . ومن خطة الدراسة أن أهالى القرية يستخدمون النظام الديني فى تطور العالم. وهناك أيضا الجوامع الإجتماعية التى تجرى فى تصميم ووسائل الأعلام التى تحتوي الإرشادات فى الفكرة الرئيسية. التصنيف والسياسة الطابعية فى فكرة من مجموع منصوص الحكم. وهذه الأحكام من تحريف العوامل الثقافية. يثبت هذا المقال على أن دين الإسلام من القائمة الخاصة لتطوير السياق الإجتماعي. والحركات الدينية تأتى مع القادمين الجدد والفكر مرافق للحركة من إجراء تحليل البيانات على النتائج . فيمكن أن يتم النظام ليس لديها تحقيقًا فى دور خاصة ولكن يدور فى الجماعات الإسلامية العامة. وبناء هذه الحطة أن تقوم فى تدريبات وتعليمات مرحلة استخدام خاصة لتحديد العوامل فى قرية معينة. وأخيرًا، يناقش هذا البحث العلاقة بين الهِمة الدينية فى اكتشاف المنظمة الإجتماعية كما أن يمكن أن تكون أساسًا للنظر فى استقبال الدراسة الأخرى لجميع المنظمات الإسلامية بين الدين والمجتمع.Abstrak: Artikel ini mengekplorasi hubungan antara masjid dengan masyarakat di Raja Ampat. Masalah penelitiannya adalah bagaimana kepedulian masyarakat dalam menjaga lingkungan yang bersumber dari ekspresi keberagamaan. Selanjutnya, penelitian ini akan menjelaskan kondisi kampung dalam menjalankan adat. Hasil penelitian menunjukkan bahwa masyarakat kampung menjadikan tradisi Islam dalam menjaga lingkungan sekitar, termasuk laut dan hutan. Aturan-aturan yang diberlakukan masyarakat untuk memandu para penduduk dalam memanen produksi lingkungan. Beberapa ide yang diterapkan dijadikan sebagai pedoman bagi setiap orang sepanjang waktu. Regulasi politik juga menjadi bagian dari dukungan terhadap praktik ini dengan diberlakukannya peraturan daerah. Peraturan tersebut diadopsi dari praktik dan kebiasaan masyarakat yang sudah berlangsung sejak dulu. Artikel ini menunjukkan bahwa Islam merupakan spirit untuk mendukung keberlangsungan kebiasaan masyarakat. Kekuatan agama menjadi dasar dalam mengatur keperluan dan pada saat yang sama mengakselerasi ide-ide baru yang diterima. Kajian ini mengkonstruksi bahwa ada beberapa kondisi setempat secara khusus membentuk pemahaman masyarakat dalam proses menjaga lingkungan. Akhirnya, artikel ini menyimpulkan bahwa agama menjadi aturan yang disinergikan dengan kebutuhan masyarakat. Penelitian ini dapat menjadi dasar bagi penelitian selanjutnya tentang ekspresi keagamaan dan penjagaan lingkungan. Keywords: sasi, masjid, adat, minoritas Muslim